2012
DOI: 10.4038/sljid.v2i2.4235
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and characteristics of Extended-Spectrum β-Lactamase producing Escherichia coli and Klebsiella species among urinary isolates in a tertiary care hospital

Abstract: A prospective study was carried out to determine the distribution of ESBL producing uropathogens in different units of a tertiary care hospital in Colombo and in community acquired UTIs presenting to this hospital. A total of 2303 urine samples from adult patients were received in the microbiology laboratory of the hospital during a four-month period, of which 626 were significant positive cultures. Escherichia coli and Klebsiella species accounted for 46% (n=286) of the total isolates with the majority (n=228… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
4
9
0
Order By: Relevance
“…Majority of culture positive patients were females (57.86%). These facts are compatible with most of previous CA-UTI studies [4].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Majority of culture positive patients were females (57.86%). These facts are compatible with most of previous CA-UTI studies [4].…”
Section: Discussionsupporting
confidence: 93%
“…In this community, ESBL producing Escherichia coli and Klebsiella pneumoniae prevalence was 40.44% while Mohomed et al in India [8] found almost same in 2007. However, according to the local study done by Dissanayake et al in 2010 [4], the ESBL prevalence found among the CA-UTI patients was 13%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The rate of ESBL producing E. coli in our study is similar to that among out patients in a tertiary care setting [20]. Previously ESBL producing E.coli was shown to be a problem in the hospital settings only, however the problem has been reported to be extending to community settings Paper as well [21].…”
Section: Discussionsupporting
confidence: 65%
“…Similar patterns of ABS has been detected in a previously conducted local study. 22 This difference is not statistically significant, but needs further study with a larger sample size and evaluation of MIC values.…”
Section: Discussionmentioning
confidence: 99%